Integrated fiscal decentralisation: taking new aid modalities to the local level - Jörg Faust; Christian von Haldenwang (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
How to combine the implementation of the new aid agenda with the challenges of advancing subsidiarityoriented decentralisation in many developing countries? This question has been neglected for some years, as most of the discussion on ownership, the use of partnercountry systems, donor harmonisation and alignment has been focused on the central government level. However, that focus tends to ignore the fact that public finance reforms in developing countries often include elements of fiscal decentralisation. Decentralisation is especially justified in many least developed countries, where it is associated with higher levels of accountability and public service provision – if implemented in an integrated manner. This being the case, we discuss opportunities for and challenges to integrated fiscal decentralisation (IFD) from a domestic and a donor perspective, considering its potential in terms of alignment, coordination and the absorption of ODA funds. ? From a domestic perspective, the core of IFD is formed by a central government transfer mechanism that allocates resources to local government bodies in accordance with a single distribution formula. The aim of this approach is to create a unified fiscal framework for local development, integrating both sectoral and regional perspectives. A broader definition of IFD includes local fiscal governance and local revenue generation. ? From the perspective of international donors, IFD offers an interesting opportunity for improving harmonisation and alignment of ODA flows. Accordingly, funds from different donors could be channelled into a nation-wide transfer (distribution) system, which would allocate resources in a transparent and accountable way. Thus an integrated perspective on fiscal decentralisation might be suitable for both reform-oriented domestic actors and for donors interested in improving international assistance. Unfortunately, promoting IFD in least developed countries has often faced all kinds of political resistance. Integrating transfers into a single formulabased distribution mechanism usually meets with opposition from those who derive greater benefit from more fragmented and discretionary transfer mechanisms, such as powerful sector ministries and some privileged subnational government bodies. Moreover, focusing on central government transfers tends to result in the important issue of local revenues being neglected. ? Therefore donors should not expect immediate and encompassing ownership of IFD reforms, but rather prepare themselves for iterative and politicised reform processes. They should not press governments to develop overly ambitious IFD blueprints: the development of context-specific and realistic sequencing strategies for IFD appears more promising. ? Furthermore, donor agencies need to pay attention to the challenge of strengthening local revenue collection rather than concentrating entirely on the reform of transfer systems and the expenditure side of local budgets.
Keywords: 330